Metallic ferromagnetism in a generalized Hubbard model - Didukh, L.; Kramar, O. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
The possibility of realization of a metallic ferromagnetic state in a generalized Hubbard model with correlated hopping and exchange interaction integrals is investigated. The single-electron energy spectrum recently obtained by means of the mean-field approximation is applied for the description of ground-state and finite-temperature properties of the system. An expression for the Curie temperature is found, and the behavior of the temperature dependences of the magnetization and paramagnetic susceptibility is analyzed. Taking into account the correlated hopping allows to explain certain peculiarities of the ferromagnetic behavior of transition metals and their compounds.